CORONARY HEART DISEASE IN PERSONS OLDER THAN 55 YEARS. PREVALENCE AND PROGNOSIS - S. A. Shalnova; A. D. Deev; A. V. Kapustina; S. E. Evstifeeva; G. A. Muromtseva; E. M. Tuaeva; Yu. A. Balanova; V. V. Konstantinov; N. V. Kiseleva; M. A. Shkolnikova (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To study prevalence of various types of coronary heart disease (CHD) and their prognostic value in men and women older than 55 y.o.Material and methods. We used the data from selections of previously diagnosed persons. Totally 1875 included, with response at 64% level. All persons were questionnaired by the standard survey, that included social and demographic data, anamnesis, Rose questionnaire, behaviour. All patients underwent ECG 12 leads. ECG analysis was done with Minnesota conding system.Results. Every 4th male and every 3rd female revealed angina pectoris by the Rose questionnaire, and 9,5% men and 2,7% women had anamnesis of infarction. Ischemic changes on ECG more often in women — 15,6% vs. 10,0% (p<0,001); and infarction itself 2 times more often affects men — 7,1% vs. 3,2% (p<0,001). For men rhythm disorders are more common, i.e. left bundle branch block (p<0,03). Overall CHD prevalence does not significantly differ between genders and is 34,6% for men and 36,0% for women. The most severe forms in account of life threatening are rhythm disorders, ischemic changes and atrial fibrillation. At the same time, for cardiovascular mortality all parameters were significant, including heart failure. By the severity of prognosis all values are spread with the same manner as for general mortality.Conclusion. CHD in older age is highly prevalent and very diverse. In women less severe forms are marked comparing to men. Epidemiologic criteria for CHD on ECG can be regarded as diagnostic and as candidates for patients stratification by the mortality risk from cardiovascular diseases and from all causes.